Manajemen Konflik Di Sekolah Menengah Kejuruan Negeri 8 Surakarta - Edy, Miftahudin; , Prof. Dr. Sutama, M.Pd; , Dr. Samino, M.M (2015)
Conflict Management in Vocational High School State of Surakarta, a thesis for getting Magister Management of Education degree at Muhammadiyah University of Surakarta 2015. The purpose of the study is to describe about: 1) The Sources of conflict; 2) the types of conflict; and 3) Management of Conflict Resolution. This type of research is qualitative. The research approach is Phenomenology. The subjects of research were principals, and teachers. Methods of data collection using in-depth interviews, observation and documentation, the technique analysis of data used triangulation. Results of the study are: 1) The sources of conflict that consist of : the of communication, the structure of organization , The human factors. 2) The kinds of conflict, the conflict within the individual, the conflict inter individual, the conflicts between the groups, and 3) The management of conflict resolution , the strategy of collaboration, The strategies of accommodation, the strategy of compromise.